Bone marrow metastasis of glioblastoma multiforme mimicking acute myeloid leukemia. Issue 6 (25th June 2020) - Nagata, Akihito; Kanemasa, Yusuke; Kikuchi, Miyu; Otani, Ryohei; Yamada, Ryoji; Motoi, Toru; Tamura, Taichi; Nakamura, Shohei; Funasaka, Chikako; Kageyama, Akihiko; Shimoyama, Tatsu; Shinoura, Nobusada; et al.
Abstract: A 46-year-old female patient with glioblastoma multiforme (GBM), IDH wild type developed severe pancytopenia 5 months after postoperative chemoradiotherapy. Bone marrow aspirate showed normocellular marrow with 70.0% abnormal cells, which suggested the possibility of acute myeloid leukemia. Immunophenotypic analysis did not show any hematological lineage markers, except for cluster of differentiation 56. The results of immunohistochemical staining of glial fibrillary acidic protein and oligodendrocyte transcription Factor 2 were positive. Based on these findings, the patient was diagnosed with bone marrow metastasis from GBM. Bone marrow metastasis from GBM is rare and little is known about the morphological characteristics of bone marrow aspiration smear findings. We experienced a rare case with marrow metastasis from GBM mimicking acute myeloid leukemia.